The significance of Hijri calendar in fiqh issues: a case of calculating hawl for zakat in Malaysia / Radzuan Nordin - Nordin, Radzuan (Academy of Contemporary Islamic Studies (ACIS), 2018)
Hijri calendar, known also as al-Qamari calendar, is yearly calendar of the Muslims as reference for many religious festives and other religious activities. Nevertheless, zakat institutions have not fully utilized Hijri calendar in matters pertaining to hawl calculation. This paper analyzed the significance of Hijri calendar in fiqh by focusing on hawl period in zakat practice. A study was conducted using data collection method from zakat institutions in Malaysia. The findings yielded that it is essential to revise the use of Hijri calendar especially for the calculation of percentage for zakat as it involves financial implications. Basically, Hijri calendar has to be given priority in the payment of zakat and its rate is 2.5 percent. However, there is a need to increase the percentage of zakat by 0.077 from 2.5 percent in calculating zakat payment if Gregorian calendar is used. This paper sheds light on confusion surrounding the Muslims in relation to the significance of Hijri calendar in current fiqh issues so as to enable them to execute the command of Allah SWT accordingly. This study is also beneficial for zakat agencies in revising their ways on calculating hawl for zakat payment. The difference between the Hijri and Gregorian calendar should be further researched and comprehended so that worship practices in relation to time period could meet the maqasid al-syar’iyyah.